2019
DOI: 10.1186/s12889-019-7622-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the impact of nutrition claims related to fat, sugar and energy content on food choices and energy intake

Abstract: Background As part of efforts to address high levels of overweight and obesity, the provision of nutrition information (e.g., through nutrition labels and nutrition claims) on food packages has increasingly become an important policy option. This study aimed to assess the influence of nutrition claims relating to fat, sugar, and energy content on product packaging on several aspects of food choices to understand how they contribute to the prevention of overweight and obesity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 47 publications
3
87
0
1
Order By: Relevance
“…In fact, some authors talk about a ‘health halo’ effect, “whereby an individual generalises from a nutrition or health claim that a product is healthier or has more favourable attributes than it actually does” [ 5 , 6 , 7 , 8 ]. Some reviews suggest that nutrition claims (NCs) can actually influence food choices [ 9 , 10 , 11 ]. Recent systematic reviews indicate that products bearing a NC have more probabilities to be chosen and that they can alter adults’ perceptions concerning the content of the products [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, some authors talk about a ‘health halo’ effect, “whereby an individual generalises from a nutrition or health claim that a product is healthier or has more favourable attributes than it actually does” [ 5 , 6 , 7 , 8 ]. Some reviews suggest that nutrition claims (NCs) can actually influence food choices [ 9 , 10 , 11 ]. Recent systematic reviews indicate that products bearing a NC have more probabilities to be chosen and that they can alter adults’ perceptions concerning the content of the products [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews indicate that products bearing a NC have more probabilities to be chosen and that they can alter adults’ perceptions concerning the content of the products [ 9 , 12 ]. Another systematic review concluded that NCs related to fat, sugar and energy content can influence the perceived healthfulness of products, making them seem healthier than they are, and thus influencing food purchase intentions [ 10 ]. Some factors related to customers may also be important to the effect of NCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential negative impact of claims on food choices and consumption [ 15 , 30 ] can be particularly significant in Mongolia. The results of this study highlight the pervasiveness of poorly regulated food claim practices.…”
Section: Discussionmentioning
confidence: 99%
“…Food labelling policy implementation, including for nutrition and health claims, has not been well studied in developing countries. Most evidence on the use of claims and their effects on diets are from developed countries [ 15 , 16 , 17 ]. The study aimed to determine the use of nutrition and health claims on packaged foods sold in Mongolia and examine the credibility of these claims.…”
Section: Introductionmentioning
confidence: 99%